Color-blind Racism in France: Bias Against Ethnic Minority Immigrants - Leland Ware (Washington University Journal of Law & Policy, 2015)
With the influx of immigrants from former French colonies in North and sub-Sarahan Africa, France’s demographic composition has changed significantly. In response to its changing demographics, France implemented veil laws under the doctrines of secularism and French Republicanism. This Article will show that France’s race-neutral policies do not prevent the bias and discrimination caused by “color-blind racism.” It examines laws, policies, and practices that disadvantage ethnic minorities in France, specifically the veil law. This Article puts those debates in a broader context by analyzing immigration policies, the effects of discrimination in housing, employment, and education, and the influence of internalized stereotypes.
Keywords: Leland Ware; France; veil laws; banlieues; ethnic minority immigration; discrimination; burqa/burka; employment discrimination; housing discrimination; education discrimination